Modeling the neodymium isotopic composition with a global ocean circulation model - Arsouze, T.; Dutay, J.-C.; Lacan, F.; Jeandel, C. (Chemical geology, 2007)
For the first time, modeling of the neodymium (Nd) isotopic composition (expressed as ε Nd) is performed in an Ocean Global Circulation Model (OPA-ORCA2.0 model). In the interest of simplicity, Nd concentration is not explicitly included and ε Nd is modeled as a passive tracer. Recent studies suggest that dissolved/particulate exchanges between continental margin sediments and seawater (termed boundary exchange, BE), could be the dominant source-sink terms that determine the distribution of neodymium isotopes in the global ocean. To test this hypothesis, we only included this BE source-sink term in the model. BE was parameterized as a relaxing term that forces ε Nd of seawater to the isotopic composition of the continental margin over a characteristic exchange time. Sensitivity tests were made using different exchange times and parameterizations. The model reproduces most of the general trends of ε Nd composition in seawater at global scale (inter-basin gradient, composition of some of the main water masses). These results suggest that BE process may account for the major sources and sinks of oceanic Nd, while indicating that the characteristic time of interaction between seawater and margins varies from about half a year in surface waters to several years at depth. The disparities between the model and observations might reflect the typical shortcomings of utilizing a coarse resolution ocean model circulation fields or neglected sources of neodymium such as dissolution of aeolian inputs or dissolved river loads.